Analysis and discussion of the rare complication of autoimmune encephalitis: Two case reports. Issue 27 (July 2018) - Li, Rong; Jiang, Li; Li, Xiu-juan; Hong, Si-qi; Zhong, Min; Hu, Yue
Abstract: Rationale: Autoimmune encephalitis related to many antibodies against neuronal cell surface or synaptic proteins, it is increasingly recognized as the cause of a variety of neuropsychiatric syndromes. Patient concerns: The two pediatric cases were about autoimmune encephalitis with rare complication. One patient was a 11-year-old girl and was diagnosed with Voltage-Gated Potassium Channel complex (VGKC) antibody-mediated encephalitis with rhabdomyolysis; the other was also a 11-year-old girl and was diagnosed with anti- N-methyl-D-aspartate receptor (NMDAR) encephalitis. Diagnoses: Both patients were diagnosed as autoimmune encephalitis with rare complication. Interventions: Intravenous methylprednisolone, oral prednisone and intravenous immunoglobulin was administered to both patients. Outcomes: One patient was discharged after a half month's hospitalization; the other was finally with intestinal function failure, gradually developed multiple organ failure, and eventually died. Lessons: The pathogenic mechanism of autoimmune encephalitis associated with autoimmune disease is not fully understood, but may be related to a common immune pathological mechanism with variance in susceptibility caused by genetic or environmental factors.